Outside In? Reflections on BMGN – Low Countries Historical Review: Introduction - Board, Editorial (BMGN - Low Countries Historical Review, 2018)
Over the last decades, the bmgn – Low Countries Historical Review has invested in a trajectory to increase the visibility of the journal beyond the Low Countries and to expand engagement with the international community working on the history of the Low Countries. The meeting of the International Advisory Board (iab) and the presentation of the first Low Countries History Award in November 2016 provided an excellent occasion to evaluate these efforts and to reflect on the strengths and weaknesses of the journal from an external perspective. We invited Ben Schmidt (University of Washington), a member of both the IAB and the jury of the Award, to reflect on the current state of the journal and to present this to the yearly conference of the Royal Netherlands Historical Society, which is responsible for publishing bmgn – Low Countries HistoricalReview. The text that follows is an edited version of this talk. This article is part of the forum 'Outside In? Reflections on BMGN – Low Countries Historical Review: Introduction'